Beyond the Colonial Phantasmagoria; Rethinking the Idea of Secular, Secular Criticism and Islam - Ali Jauhar Changarath (LECTURES: Journal of Islamic and Education Studies, 2025)
The tendencies of recalling and rethinking identity formation while remaining in the liminal space of the colonial matrix, are themselves the constructs of a particular language in itself. The decolonial theory was formed as part of standing beyond this particular language. In this perspective we can see numerous works conceptualizing the notions of meta-narratives outside the colonial matrix. This paper explores such dialogues and interpretations towards secularism and secular critic and approaches which place them in a broad sense of religion beyond the colonial perspective.